Síntese de derivados vinílicos e enínicos de fósforo e aplicação sintética de dissulfetos imidazolidínicos quirais em reações assimétricas - Andrade, Leandro Helgueira de (2002)
In this work, we developed a method to prepare β-alkynylvinylphosphonates 3 via a palladium-catalyzed cross-coupling reaction of β-n-butyltellurovinylphosphonates 2 with terminal alkynes. The compounds 2 were prepared by addition of an organyltellurolate anion to 1-alkynylphosphonates 1, according to a method developed in our MSc. Dissertation. By analogous reactions, we were able to synthesize vinylphosphine oxides 5 and β-alkynylvinylphosphine oxides 6. [...]